PROBLEMATIKA KERJASAMA GURU BIMBINGAN KONSELING DENGAN GURU MATA PELAJARAN DI MTS NEGERI MULAWARMAN BANJARMASIN - Dian Wulandari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2015)
AbstractIssues to be observed is a form of cooperative relationship BK teachers with subject teachers at MTs Mulawarman Banjarmasin views of management principles, factors that support and hinder cooperation as well as cooperation in related management principles, efforts are being made to increasing support in cooperation BK teachers and subject teachers, attempts are being made to overcome the barriers to cooperation BK teachers and subject teachers at MTs Mulawarman Banjarmasin. The population in this study are all subject teachers who numbered 52 people and counseling teachers (BK) total of 3 people at MTs Mulawarman Banjarmasin. The samples were taken by 50% using the theory Winarno Surakhmad with random cluster sampling technique which means that researchers will not examine all the objects in the population, but using as a representative sample of the population. Data extracted by observation and interviews as the main data collection tool, as well as a method of supporting documentation. Processing and analysis of data using ways encapsulates all the interviews that have been done, then compiled and analyzed. The results of this study indicate that the cooperation counseling teachers (BK) with subject teachers at MTs Mulawarman Banjarmasin did not go well, less harmonious, and not in accordance with the principles of management. Factors supporting the cooperation and its implementation are: routine activities such as flag-raising ceremony, religious activities and activities of the Olympic championship. Inhibiting factors are: the existence of guidance and counseling teachers (BK) were not considered, as well as the takeover of the duties and functions by the subject teachers. Efforts were made to increase support in co-operation such as: held a consultation led by the Principal. Later efforts to overcome barriers to cooperation: a meeting with the entire board of teachers, and chaired by the Principal. Keywords: Problems, Teacher Counseling, Subject Teacher.